Ellagic Acid Alleviates Oxidative Stress by Mediating Nrf2 Signaling Pathways and Protects against Paraquat-Induced Intestinal Injury in Piglets - Yuxin Xiao; Rui Huang; Nan Wang; Yuankun Deng; Bie Tan; Yulong Yin; Ming Qi; Jing Wang (MDPI AG, 2022)
The gastrointestinal tract is a key source of superoxide so as to be one of the most vulnerable to oxidative stress damage. Ellagic acid (EA), a polyphenol displays widely biological activities owing to its strong antioxidant properties. Here, we investigated the protective benefits of EA on oxidative stress and intestinal barrier injury in paraquet (PQ)-challenged piglets. A total of 40 weaned piglets were randomly divided into five groups: Control, PQ, 0.005% EA-PQ, 0.01% EA-PQ, and 0.02% EA-PQ. Piglets were intraperitoneally injected with 4 mg/kg (BW) PQ or saline on d-18, and sacrificed on d-21 of experiment. EA treatments eliminated growth-check induced by PQ and increased serum superoxide dismutase (SOD) activity but decreased serum malondialdehyde (MDA) level as compared to PQ group. EA supplementation promoted Nrf2 nuclear translocation and enhanced heme oxygenase-1 (HO-1) and quinone oxidoreductase 1 (NQO1) protein abundances of small intestinal mucosa. Additionally, EA improved PQ-induced crypt deepening, goblet cells loss, and villi morphological damage. Consistently, EA increased tight junction protein expression as was evident from the decreased serum diamine oxidase (DAO) levels. EA could ameliorate the PQ-induced oxidative stress and intestinal damage through mediating Nrf2 signaling pathway. Intake of EA-rich food might prevent oxidative stress-mediated gut diseases.